A novel AVPR2 gene mutation of X-linked congenital nephrogenic diabetes insipidus in an Asian pedigree. (October 2016) - Guo, Wei-Hong; Li, Qiang; Wei, Hong-Yan; Lu, Hong-Yan; Qu, Hui-Qi; Zhu, Mei
Polyuria and polydipsia are the characteristics of congenital nephrogenic diabetes insipidus (CNDI). Approximately 90% of all patients with CNDI have X-linked hereditary disease, which is due to a mutation of the arginine vasopressin receptor 2 ( AVPR2 ) gene. This case report describes a 54-year-old male with polyuria and polydipsia and several male members of his pedigree who had the same symptoms. The proband was diagnosed with diabetes insipidus using a water-deprivation and arginine vasopressin stimulation test. Genomic DNA from the patient and his family members was extracted and the AVPR2 gene was sequenced. A novel missense mutation of a cytosine to guanine transition at position 972 (c.972C > G) was found, which resulted in the substitution of isoleucine for methionine at amino acid position 324 (p.I324M) in the seventh transmembrane domain of the protein. The proband's mother and daughter were heterozygous for this mutation. The novel mutation of the AVPR2 gene further broadens the phenotypic spectrum of the AVPR2 gene.